Financial Reporting Environments and International Capital Mobility - Young, Danqing; Guenther, David A. (Journal of Accounting Research, 2003)
abstract We examine whether differences in international capital mobility across countries are related to country‐specific differences in financial reporting environments. We hypothesize that countries where financial accounting environments lead to greater disclosure of value‐relevant accounting information are more likely to have higher international capital mobility. The results of empirical tests are consistent with our hypothesis.